Factors determining the means of suicide among suicidal patients treated by mobile emergency medical services in Brazil - Meneguin, Silmara [UNESP]; Afonso, Maria Gabriela [UNESP]; Almeida, Priscila Masquetto Vieira de; Morais, José Fausto de; Pollo, Camila Fernandes [UNESP]; Oliveira, Cesar de (Springer Nature, 2025)
ObjectiveTo analyse the factors associated with the means of suicide in suicidal patients treated by mobile emergency medical services (EMS) in the Botucatu and Ourinhos regions of São Paulo state, Brazil.MethodsA retrospective and comparative study was conducted to analyse 807 cases of attempted suicide treated by EMS teams from 2018 to 2019.ResultsOverall, exogenous intoxication (53%), patients aged 24 or older (64.4%), women (65.2%), and individuals who survived the occurrence (97.9%) predominated in both regions. The multiple multinomial logistic regression analysis revealed that poisoning was associated with age (OR = 1.042, 95% CI: 1.006 to 1.079; p = 0.021); suicidal ideation was associated with summer (OR = 3.001, 95% CI: 1.993 to 4.518; p < 0.001), the Botucatu region (OR = 28.143, 95% CI: 11.229 to 70.537; p < 0.001), and female sex (OR = 0.586, 95% CI: 0.385 to 0.892; p = 0.013); self-aggression was associated with the Botucatu region (OR = 5.688, 95% CI: 2.925 to 11.057; p < 0.001); and hanging was associated with female sex (OR = 0.488, 95% CI: 0.279 to 0.854; p = 0.012). Furthermore, being female (OR = 0.367, 95% CI: 0.140 to 0.961; p = 0.041), residing in the Botucatu region (OR = 0.123, 95% CI: 0.050 to 0.299; p < 0.001), and exogenous intoxication (OR = 0.014, 95% CI: 0.002 to 0.110; p < 0.001) were identified as protective factors related to the outcome of death.ConclusionRecognising multiple factors intrinsic to individual and environmental influences associated with the means of suicide used by suicidal patients treated by EMS teams highlights the importance of rapid, effective care provided by pre-hospital emergency teams for preventing deaths. The protective factors identified include being female, being from the Botucatu region, and experiencing exogenous intoxication.DescriptorsSuicide; Attempted Suicide; Emergency Medical Services; Death; Cause of Death.